2015
DOI: 10.1016/j.ultsonch.2014.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of particle size and molecular interactions by sonoprecipitation method for enhancing dissolution rate of poorly water-soluble drug

Abstract: Aim of present work was to originally elucidate the roles of ultrasonication method for modulating the size and molecular interactions in controlling release of poorly water-soluble drug. Curcumin was chosen as a model drug. Three types of polymers were investigated as carriers for preparation of polymeric nanoparticles under various ultrasonication conditions and polymer-drug ratios. Changes in drug crystallinity, particle size, and molecular interactions which would be factors enhancing drug dissolution rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Effective delivery of Biopharmaceutics Classification System class II active pharmaceutical ingredients (APIs), defined as having high permeability and low solubility, 1 is challenging due to their low bioavailability. 2 To enhance their bioavailability, several technologies have been examined, such as particle size reduction, [3][4][5] cyclodextrin complexes, 6 polymeric micelles, 7 freeze-dried liposomes, 8 solid lipid nanoparticles, 9 and amorphous solid dispersions (ASDs). 10,11 Among them, amorphous solids dispersions technology has been proved to be one of the promising solutions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective delivery of Biopharmaceutics Classification System class II active pharmaceutical ingredients (APIs), defined as having high permeability and low solubility, 1 is challenging due to their low bioavailability. 2 To enhance their bioavailability, several technologies have been examined, such as particle size reduction, [3][4][5] cyclodextrin complexes, 6 polymeric micelles, 7 freeze-dried liposomes, 8 solid lipid nanoparticles, 9 and amorphous solid dispersions (ASDs). 10,11 Among them, amorphous solids dispersions technology has been proved to be one of the promising solutions.…”
Section: Introductionmentioning
confidence: 99%
“…26 Fine APIs are widely used for enhancement of available surface areas and hence dissolution rates. 4,[27][28][29][30] In addition, faster dissolution rates result in shorter residence time of API powders in the dissolution media, which is expected to reduce the time available for recrystallization of ASDs. This may in turn lower the amounts of polymeric crystallization inhibitor needed.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, solubility of CUR at pH 1.2 and pH 6.8 were 7.230 AE 0.35 and 12.6 23 AE 3.54, respectively. For this reason, most dissolution release rate of CUR from SDs in the current studies in intestinal fluid (pH 6.8) was faster than that in gastric fluid (pH 1.2) and the percentage of pure CUR released in these media was under 5% in previous studies (Tran et al, 2015). Therefore, the improvement of dissolution rate in these conditions was discovered.…”
Section: Dissolution and Solubility Studiesmentioning
confidence: 56%
“…It has been also reported that sonication process was very effective to decrease particle size and produce homogeneous colloidal system by reducing agglomeration through management of nucleus growth condition and population (Luque de Castro and Priego‐Capote ; Vasconcelos and others ; Abbas and others ). Reduced particle size may improve water solubility and dissolution rate of the water insoluble compounds which can correlate with substantial enhancement of oral bioavailability (Tran and others ). PDI values were also significantly decreased after UH and maintained less than 0.3 which means that Cur‐TPGS NSs were maintained in high homogeneity after UH.…”
Section: Resultsmentioning
confidence: 99%